Effect of TB/HIV Integration on TB and HIV indicators in Rural Ugandan Health Facilities - BURNETT, Sarah M (J Acquir Immune Defic Syndr, 2018)
BACKGROUND: WHO recommends integrating services for patients co-infected with TB and HIV. We assessed the effect of TB/HIV integration on ART initiation and TB treatment outcomes among TB/HIV co-infected patients using data collected from 14 rural health facilities during two previous TB and HIV quality of care studies. METHODS: A facility was considered to have integrated TB/HIV services if TB/HIV patients had combined treatment for both illnesses by one provider or care team at one treatment location. We analyzed the effect of integration by conducting a cross-sectional analysis of integrated and non-integrated facility periods comparing performance on ART initiation and TB treatment outcomes. We conducted logistic regression, with the patient as the unit of analysis, controlling for other intervention effects, adjusting for age and gender, and clustering by health facility. RESULTS: From January 2012-June 2014, 996 TB patients were registered, 97% were tested for HIV and 404 (42%) were HIV positive. Excluding transfers, 296 patients were eligible for analysis with 117 and 179 from non-integrated and integrated periods, respectively. Being treated in a facility with TB/HIV integration was associated with lower mortality (adjusted odds ratio [aOR]=0.38, 95% confidence interval [CI]=0.18–0.77), but there was no difference in the proportion initiating ART (aOR=1.34, 95% CI=0.40–4.47), with TB treatment success (aOR=1.43, 95% CI=0.73–2.82), lost to follow-up (aOR=1.64, 95% CI=0.53–5.04), or failure (aOR=1.21, 95% CI=0.34–4.32). CONCLUSION: TB/HIV service integration was associated with lower mortality during TB treatment even in settings with suboptimal proportions of patients completing TB treatment and starting on ART.